2021
DOI: 10.1029/2021jd034648
|View full text |Cite
|
Sign up to set email alerts
|

WRF Gray‐Zone Simulations of Precipitation Over the Middle‐East and the UAE: Impacts of Physical Parameterizations and Resolution

Abstract: Several single-year-long (2017) simulations with different configurations of the Weather Research and Forecasting (WRF) model over the United Arab Emirates (UAE) and the Middle-East at the convective gray-zone resolution (9 km) are evaluated in their ability to capture the temporal and spatial distributions of precipitation. Annual rainfall over the Middle-East is dominated by wintertime precipitation and is mostly initiated by the frontal systems intrusion. WRF at 9 km resolution shows good skill in capturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 78 publications
(94 reference statements)
1
17
0
Order By: Relevance
“…Taraphdar et al. (2021) demonstrated that model simulations over the UAE using ERA‐5 temperature and moisture fields for forcing the initial and boundary conditions outperformed other reanalysis products. Similarly, Tahir et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taraphdar et al. (2021) demonstrated that model simulations over the UAE using ERA‐5 temperature and moisture fields for forcing the initial and boundary conditions outperformed other reanalysis products. Similarly, Tahir et al.…”
Section: Methodsmentioning
confidence: 99%
“…To present the overall synoptic conditions during the fog events, the ERA-5 reanalysis data from the European Centre for Medium Weather Forecast (Hersbach et al, 2020) is employed in this study. This data set is selected given its higher spatial (0.25°, about 27 km) and temporal (hourly) resolution compared to other reanalysis datasets, in addition to its superior performance in the region (e.g., Mahto & Mishra, 2019;Tahir et al, 2020;Taraphdar et al, 2021). Taraphdar et al (2021) demonstrated that model simulations over the UAE using ERA-5 temperature and moisture fields for forcing the initial and boundary conditions outperformed other reanalysis products.…”
Section: Reanalysis Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The physics schemes selected reflect the findings of Schwitalla et al (2020) and Francis, Chaboureau, et al (2021). Given the crucial role of the PBL scheme on the model-predicted convection and precipitation in the UAE, as highlighted by Taraphdar et al (2021), three PBL schemes are considered in this work: Mellor-Yamada Nakanishi Niino (MYNN; Nakanishi & Niino, 2006; Yonsei University (YSU; Hong et al, 2006); Asymmetric Convective Model 2 (ACM2; Pleim, 2007aPleim, , 2007b. PBL schemes differ in the way the turbulent fluxes, which arise when the Reynolds decomposition is applied to the primitive equations, are parameterized (Cohen et al, 2015(Cohen et al, , 2017.…”
Section: Numerical Modelmentioning
confidence: 99%
“…The authors stressed that Local PBL schemes showed better performance compared to non-local schemes. On a larger scale, Taraphdar et al [39] conducted a sensitivity study to assess the impact of physical parameterizations and model resolution on precipitation simulations over the UAE and the Middle East at the convective gray-zone resolution.…”
Section: Introductionmentioning
confidence: 99%